2022
DOI: 10.1136/bmjopen-2021-053375
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of depression symptoms among rural and urban populations affected by Ebola virus disease in the Democratic Republic of the Congo: a representative cross-sectional study

Abstract: ObjectivesHigh mortality rates, anxiety and distress associated with Ebola virus disease (EVD) are risk factors for mood disorders in affected communities. This study aims to document the prevalence and risk factors associated with depressive symptoms among a representative sample of individuals affected by EVD.DesignCross-sectional study.SettingThe current study was conducted 7 months (March 11, 2019 to April 23, 2019) after the end of the ninth outbreak of EVD in the province of Equateur in the Democratic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Using the Statistical Package for the Social Sciences (SPSS), version 27, we computed the prevalence of severe symptoms of PTSD and anxiety using the above-mentioned cut-off across sociodemographic characteristics including gender, age category, education level, employment status, categories of exposure to EVD and COVID-19, and categories of stigmatization due to EVD and COVID-19. To compare levels of exposure to EVD and COVID-19 and stigmatization related to EVD and COVID-19, their scores were classified in four categories with values below the 25th percentile, between the 25th and 50th percentile, between 50th and 75th, and values beyond the 75th percentile according to past studies (13)(14)(15)20). Subsequently, a multivariable linear regression was conducted separately to examine the association between mental health symptoms (PTSD and anxiety) and exposure to EVD, exposure to COVID-19, and stigmatization due to EVD and COVID-19.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Statistical Package for the Social Sciences (SPSS), version 27, we computed the prevalence of severe symptoms of PTSD and anxiety using the above-mentioned cut-off across sociodemographic characteristics including gender, age category, education level, employment status, categories of exposure to EVD and COVID-19, and categories of stigmatization due to EVD and COVID-19. To compare levels of exposure to EVD and COVID-19 and stigmatization related to EVD and COVID-19, their scores were classified in four categories with values below the 25th percentile, between the 25th and 50th percentile, between 50th and 75th, and values beyond the 75th percentile according to past studies (13)(14)(15)20). Subsequently, a multivariable linear regression was conducted separately to examine the association between mental health symptoms (PTSD and anxiety) and exposure to EVD, exposure to COVID-19, and stigmatization due to EVD and COVID-19.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This double crisis could reignite both the fear of survivors and HCWs, and the stigmatization to which they have been subjected to according to a process of retraumatization (12). Studies conducted during the first wave of the COVID-19 pandemic in several countries, including the DRC, showed that stigmatization related to the disease was the most significant predictor of mental health problems, including anxiety and depression (13)(14)(15). In addition, the eastern region of the DRC has been facing armed conflicts for over 20 years (16).…”
Section: Introductionmentioning
confidence: 99%
“… 5. Cenat J. M. 2022 34 Equateur, DRC. 1614 adults affected by the ninth month of Ebola outbreak Investigate the prevalence of, and risk factors associated with, depressive symptoms among individuals affected by Ebola Virus Disease (EVD) Multivariable logistic regression EVD exposure level, stigmatization related to EVD and Beck Depression Inventory-Short Form (BDI-SF) Adults in the two higher score categories of exposure to EVD were at two times higher risk of developing severe depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Stressful life events were assessed using the Impact of Event Scale revised version (IES-R) 29 . To assess stigma, a 20-item scale that measures 20 possible forms of stigmatization related to Ebola Virus Disease (EVD) was used 34 . Most instrument measures used multiple items to assess participants’ mental health and other conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Stigma associated with infectious disease outbreaks reduces affected persons’ opportunities for physical, social, and psychological well-being, contributing to social and health inequalities ( 8 11 ). COVID-19 and Ebola virus disease (EVD) stigmatization have specifically been proven predictors of severe psychological distress, depression, anxiety, and posttraumatic stress disorder symptoms ( 1 , 11 13 ). Stigma can also impede efforts to control disease outbreaks by fueling fear, decreasing uptake of preventive measures (including vaccination), discouraging health-seeking behavior such as seeking testing and treatment, and reducing adherence to care ( 6 , 8 , 10 , 14 ).…”
mentioning
confidence: 99%